The application of artificial intelligence in the context of the educational system in Serbia, with a special focus on religious education - Tomić, Bojan; Radovanović, Nebojša (Sociološki pregled, 2024)
The presence and increasing influence of artificial intelligence (AI) in modern society and its already acknowledged potential for transforming educational practice demand a thorough and systematic study of the implications of its use in the entire educational system, aa well as in the context of certain school subjects and curricula. This paper covers the theoretical and empirical frameworks for analyzing positive and negative aspects of AI integration into education, with a special focus on religious education. In the theoretical segment, AI possibilities and challenges are analyzed in the context of today’s teaching process, while the empirical part of the research is focused on analyzing the aspects of AI application in the organization of the teaching process for the optional subject Religious Education. By identifying advantages and challenges in the application of this technology, AI possibilities are considered in detail as an auxiliary instrument for preparing Religious Education lessons in the primary school. For that purpose, the answers generated by ChatGPT application were compared with the subject teacher’s experience about the lesson preparation, whereas apart from content overlapping, deviation was also observed in the quality of certain generated answers. Through a critical review of the current situation in AI use in education, this paper offers a general estimate of the current situation, recognizing the importance of further development and adaptation of pedagogical practices to AI possibilities.